PENGARUH STRUKTUR KEPEMILIKAN, ATRIBUT DEWAN, DAN RISIKO KEBANGKRUTAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN: PERAN MODERASI KONVERGENSI IFRS - Ariani, Desi; Fuad, Fuad (Diponegoro Journal of Accounting, 2024)
This study aims to examine the impact of ownership structure, board attributes, and bankcruptcy risk indicators on the timeliness of financial reporting with IFRS comvergence as a moderating variable. The independent variables used in this study are the foreign ownership, institutional ownership, board size, independent board membership, gender diversity, and bankcruptcy risk indicators. While the dependent variable used in this studyis the timeliness of financial reporting an IFRS convergence as the moderating variable in this study.The population in this study consist of mining companies that are listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. Purposive sampling is used to as the sampling method. This study uses panel data regression to examine ownership structure which consists foreign ownership and institutional ownership, board attributes which consists board size and independent board membership, gender diversity and bankcruptcy risk indicators on the timeliness of financial reporting and testing the moderating variable using the Moderated Regression Analysis.The results show that foreign ownership, board size, and bankcruptcy risk indicators have a significant effect on the timeliness of financial reporting, while institutional ownership, independent board membership, and gender diversity have no significant effect on the timeliness of financial reporting. IFRS convergence does not moderate the relationship that exist between foreign ownership, institutional ownership, board size, independent board membership, gender diversity, and bankcruptcy risk indicators with the timeliness of financial reporting.